Stoppa Approach for Anterior Plate Fixation in Unstable Pelvic Ring Injury - Oh, Hyoung-Keun (Clin Orthop Surg, 2016)
BACKGROUND: The Stoppa (intrapelvic) approach has been introduced for the treatment of pelvic-acetabular fractures; it allows easy exposure of the pelvic brim, where the bone quality is optimal for screw fixation. The purpose of our study was to investigate the surgical outcomes of unstable pelvic ring injuries treated using the Stoppa approach for stable anterior ring fixation. METHODS: We analyzed 22 cases of unstable pelvic ring injury treated with plate fixation of the anterior ring with the Stoppa approach. We excluded cases of nondisplaced rami fracture, simple symphyseal diastasis, and parasymphyseal fractures, which can be easily treated with other techniques. The average age of the study patients was 41 years (range, 23 to 61 years). There were 10 males and 12 females. According to the Young and Burgess classification, there were 12 lateral compression, 4 anteroposterior compression, and 6 vertical shear fracture patterns. The fracture location on the anterior ring was near the iliopectineal eminence in all cases and exposure of the pelvic brim was required for plate fixation. All patients were placed in the supine position. For anterior plate fixation, all screws were applied to the anterior ramus distally and directed above the hip joint proximally. Radiologic outcomes were assessed by union time and quality of reduction by Matta method. The Merle d'Aubigne-Postel score was used to evaluate the functional results. RESULTS: The average radiologic follow-up period was 16 months (range, 10 to 51 months). All fractures united at an average of 3.5 months (range, 3 to 5 months). According to the Matta method, the quality of reduction was classified as follows: 16 anatomical (73%) and 6 nearly anatomical (27%) reductions. There were no cases of screw or implant loosening before bone healing. The functional results were classified as 7 excellent (32%), 12 good (55%), and 3 fair (13%) by the Merle d'Aubigne-Postel score. There were no wound complications, neurovascular injuries, or other complications related to the surgical approach. CONCLUSIONS: Stable anterior ring fixation placed via the Stoppa approach can result in excellent reduction and stable screw fixation with a low complication rate.